Downregulated endogenous sulfur dioxide/aspartate aminotransferase pathway is involved in angiotensin II-stimulated cardiomyocyte autophagy and myocardial hypertrophy in mice. (15th December 2016) - Chen, Qinghua; Zhang, Lulu; Chen, Siyao; Huang, Yaqian; Li, Kun; Yu, Xiaoqi; Wu, Huijuan; Tian, Xiaoyu; Zhang, Chunyu; Tang, Chaoshu; Du, Junbao; Jin, Hongfang
Abstract: Background: The study was designed to investigate if endogenous sulfur dioxide (SO2 ) was involved in cardiomyocyte autophagy and myocardial hypertrophy stimulated by angiotensin II (Ang II). Methods: Thirty-two C57 mice were randomly divided into control, SO2, Ang II and Ang II + SO2 groups. Human myocardial cell line H9c2 was divided into four groups including control, SO2, Ang II and Ang II + SO2 groups. Blood pressure and myocardial hypertrophy of the mice were measured two weeks after Ang II administration. LC3 II/I ratio, and Beclin1, Atg4B and p62 expressions were determined both in vivo and in vitro . Autophagosome was observed in H9c2 cells with confocal microscope. Endogenous SO2 generation and aspartate aminotransferase (AAT) expression were measured. Results: In animal studies, hypertension and myocardial hypertrophy developed two weeks after Ang II administration. LC3 II/I ratio and Beclin1 and Atg4B expressions were markedly elevated ( P all < 0.05), but p62 expression was lowered ( P < 0.05) both in vivo and in vitro . Compared with control group, endogenous SO2 levels, AAT activity and AAT2 expression were obviously down-regulated ( P all < 0.05). However, SO2 donor significantly reduced Ang II-induced myocardial hypertrophy in mice. LC3 II/I ratio and Beclin1 and Atg4B expressions were down-regulated ( P all < 0.05) but p62 expression was significantly increased ( P < 0.05) in the presence of SO2 both in vivo and in vitro . Conclusion: Down-regulated endogenous SO2 /AAT2 pathway might be involved in the pathogenesis of myocardial hypertrophy. SO2 prevented Ang II -induced myocardial hypertrophy accompanied by down-regulating cardiomyocyte autophagy.